The Development of Corporate Social Responsibility in the Context of Overcoming a Welfare State Crisis: a Theoretical and Empirical Analysis - Nadiia Grazhevska; Alla Mostepaniuk (Comparative Economic Research. Central and Eastern Europe, 2021)
The current social crisis, caused by the negative consequences of globalization, labor migration, and an aging population, requires the state's role in economic and social spheres to be reconsidered. In order to achieve and maintain sustainable economic growth, the pressing social problems, such as poverty, hunger, discrimination, and the unequal distribution of income, should be solved. Under these circumstances, the pa- per investigates the process of forming a welfare state to evaluate the role of current states in this period of social crisis. To achieve the aim, the following methods were used: historical and systematic analysis of the scientific literature and socio-economic conditions of the evolution of theoretical approaches of the welfare state, and the causes and characteristics of the present social crisis; cluster analysis of European countries to find similar patterns based on the level of corporate social responsibility (CSR) development, state social expenditures, and the government budget balance. The paper contains a detailed analysis and discussion of the formation of a welfare state. The study concludes that the process of delegating some state social services to the private sector in the form of CSR can be considered an efficient mechanism to eliminate and overcome the current social crisis through the accumulation of social capital. At the same time, the results of the cluster analysis of European countries demonstrated the importance of CSR development as a compensator for the negative effects of a public welfare crisis and for solving pressing social problems in most Eu- ropean countries. Specific features of post-socialist countries in the context of social orientation of state policy and the development of CSR are highlighted.
Keywords: I38; M14; 330; welfare state; social crisis; social policy; social protection; corporate social responsibility